1983
DOI: 10.1113/jphysiol.1983.sp014661
|View full text |Cite
|
Sign up to set email alerts
|

Colonic motility and transit of digesta during hard and soft faeces formation in rabbits.

Abstract: SUMMARY1. Rabbits produce hard and soft faeces in a circadian rhythm. This study was undertaken in order to examine the motor function of the colon in relation to the formation of these two types of faeces.2. Colonic motility was measured in unanaesthetized rabbits using strain-gauge transducers and simultaneous radiography.3. Three types of contractions were found in the rabbit proximal colon: haustral activity, segmental activity, and mass peristalsis. Distinctly different motor patterns were observed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
59
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 7 publications
4
59
0
1
Order By: Relevance
“…It is likely that different conditions of the luminal content (e.g., greater volume or viscosity) would generate neurally dependent movements on the oral side of the transition zone (28). The CMMCs in this study were found to propagate all the way along the single tenia region of the proximal colon to the colonic flexure (fusus coli) at a remarkably constant velocity, similar to those reported previously as "haustral progression" at 0.1 mm/s (28) and as "segmental contractions" at 0.1-0.3 mm/s (16,17). The characteristics of CMMCs in rabbit colon were similar to those described in other species (6,13,36,37,40).…”
Section: Neurogenic Migrating Motor Complexes In the Proximal Colonsupporting
confidence: 74%
See 4 more Smart Citations
“…It is likely that different conditions of the luminal content (e.g., greater volume or viscosity) would generate neurally dependent movements on the oral side of the transition zone (28). The CMMCs in this study were found to propagate all the way along the single tenia region of the proximal colon to the colonic flexure (fusus coli) at a remarkably constant velocity, similar to those reported previously as "haustral progression" at 0.1 mm/s (28) and as "segmental contractions" at 0.1-0.3 mm/s (16,17). The characteristics of CMMCs in rabbit colon were similar to those described in other species (6,13,36,37,40).…”
Section: Neurogenic Migrating Motor Complexes In the Proximal Colonsupporting
confidence: 74%
“…Ehrlein described in vivo myogenic contractions with mainly retrograde propagation, which he called "haustral activity with rolling movements" (16). As Ehrlein suggested (16), it seems likely that myogenic ripples are primarily involved in mixing rather than propulsion of content.…”
Section: Myogenic Motor Activity In All Regions Of Rabbit Colonmentioning
confidence: 99%
See 3 more Smart Citations